Isolation and characterization of a high-efficiency algicidal bacterium Pseudoalteromonas sp. LD-B6 against the harmful dinoflagellate Noctiluca scintillans - Wang, Junyue; Yin, Xueyao; Xu, Mingyang; Chen, Yifan; Ji, Nanjing; Gu, Haifeng; Cai, Yuefeng; Shen, Xin (Frontiers in Microbiology, 2022)
The dinoflagellate Noctiluca scintillans is a harmful algal species that is globally distributed and poses a certain threat to marine ecosystems. Recent research has shown that the application of algicidal bacteria is a promising method to prevent and control such harmful algal blooms (HABs), given its advantages of safety and efficiency. In this study, a strain of algicidal bacterium LD-B6 with high efficiency against N. scintillans was isolated from the coastal waters of Lianyungang, China. 16S rDNA sequence analysis showed that the strain LD-B6 belongs to the genus Pseudoalteromonas. Furthermore, the algicidal effect of LD-B6 on N. scintillans was investigated. The results showed that strain LD-B6 exerted strong algicidal activity against N. scintillans. After 12 h of bacterial culture addition to algal cultures at a 2% final volume rate, the algicidal activity reached 90.5%, and the algicidal activity of LD-B6 was influenced by the density of N. scintillans. In addition, the algicidal bacterium LD-B6 was found to indirectly lyse algal cells by secreting extracellular compounds. These algicidal compounds were stable, indicating that they are not proteins. Importantly, strain LD-B6 was broadly general, showing varying degrees of lysing effects against five of the six algal species tested. On the basis of the described studies above, the algicidal powder was also initially developed. In summary, the isolated bacterial strain LD-B6 shows the potent algicidal capability to serve as a candidate algicidal bacterium against N. scintillans blooms.